Male Diagnosis of the Female Pen in Late Victorian Britain: Private Assessments of Supernatural Religion - Cadwallader, Alan H. (Journal of Anglican studies, 2007)
Anonymity is a feature of the explosion of publications in nineteenthcentury England. Its motivations were variegated just as efforts to expose an anonymous author were also driven by a variety of agendas. One of the longest retentions of anonymity attached to a work that profoundly disturbed Victorian religiosity was the threevolume book titled Supernatural Religion. The Dublin Divinity Professor, George Salmon's private correspondence with Bishop J.B. Lightfoot near the end of Lightfoot's life posited the author as a woman, Mrs Humphry Ward. An analysis of Salmon's letters is set into the context of the private and public writings of key protagonists in the debates, and reveals deep-seated attitudes about gender, learning, writing, national identity, morality and anonymity in some elite intellectual circles of the society and church of the time.